2018
DOI: 10.3892/ol.2018.8284
|View full text |Cite
|
Sign up to set email alerts
|

Addition of bevacizumab to systemic therapy for locally advanced and metastatic nasopharyngeal carcinoma

Abstract: Radiotherapy is a vital treatment option for patients with nasopharyngeal carcinoma (NPC). Concurrent cisplatin-based radiochemotherapy with or without adjuvant chemotherapy had acquired good clinical effects with good local control rates. However, a number of patients present with metastasis following systemic regimens or initial diagnosis of locally advanced NPC, which cause difficulty for subsequent therapy. Therefore, there is an urgent requirement to discover novel targeted therapies. The present report d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 52 publications
(89 reference statements)
0
2
0
Order By: Relevance
“…In recent years, targeted therapy has become a promising anti-tumor treatment method. Researches have demonstrated that anti-angiogenic drugs and chemoradiotherapy have a synergistic effect on NPC (Lee et al 2012 ; Zhang et al 2018 ). Currently, the application of Endostar in NPC mainly focused on recurrent and metastatic patients (Guan et al 2015 ; Jin et al 2013 ), and had improved the complete remission rate of CLNs metastasis (Li et al 2020a , b ).…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, targeted therapy has become a promising anti-tumor treatment method. Researches have demonstrated that anti-angiogenic drugs and chemoradiotherapy have a synergistic effect on NPC (Lee et al 2012 ; Zhang et al 2018 ). Currently, the application of Endostar in NPC mainly focused on recurrent and metastatic patients (Guan et al 2015 ; Jin et al 2013 ), and had improved the complete remission rate of CLNs metastasis (Li et al 2020a , b ).…”
Section: Discussionmentioning
confidence: 99%
“…Bevacizumab, a monoclonal antibody targeting VEGF, effectively inhibits VEGF activity, thereby achieving the objectives of anti-tumor angiogenesis and metastasis suppression in NPC ( 97 ). This therapy can be used for the treatment of locally advanced and metastatic NPC ( 98 100 ). Recent studies have demonstrated that Endostar, a recombinant human endostatin, is a targeted drug with antiangiogenic and antitumor effects, and when combined with other antitumor therapies, it significantly enhances the overall anticancer effect ( 101 , 102 ).…”
Section: Angiogenic Application In Npcmentioning
confidence: 99%